Barriers to Business Process Innovation in Public Service Organizations - Qiyamullaily, Arista; Susanto, Tony Dwi; Mahendrawathi, ER (Universitas Bina Darma, 2024)
This study aims to identify the main barriers in implementing business process innovation in government organizations using the Systematic Literature Review (SLR) method. The barriers were categorized into four aspects: people, technology, structure, and process, in accordance with the Socio-Technical Theory approach. The results show that a lack of knowledge and training related to innovation, limited funding, and inadequate technological infrastructure are the dominant barriers. In addition, complex bureaucracy and lack of structured processes are also significant barriers. The research recommends a holistic approach that includes improved communication, training, technology investment, as well as bureaucratic reform to foster more effective innovation. The findings provide a basis for better policy-making and emphasize the importance of further research to understand and address barriers to innovation in different countries.